How to make farming and agricultural extension more nutrition-sensitive: Evidence from a randomized controlled trial in Kenya - Sylvester Ochieng Ogutu; Andrea Fongar; Theda Gödecke; Lisa Jäckering; Henry Mwololo; Michael Njuguna; Meike Wollni; Matin Qaim (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2018)
We analyze how agricultural extension can be made more effective in terms of increasing smallholder farmers' adoption of pro-nutrition technologies, such as biofortified crops. In a randomized controlled trial with farmers in Western Kenya, we implemented several extension treatments and evaluated their effects on the adoption of beans that were biofortified with iron and zinc. Difference-in-difference estimates show that intensive agricultural training tailored to local conditions can increase technology adoption considerably. Within less than one year, adoption of biofortified beans increased from almost zero to more than 20%. Providing additional nutrition training further increased adoption by another 10-12 percentage points, as this has helped farmers to better appreciate the technology's nutritional benefits. These results suggest that effective nutrition training through agricultural extension services is possible. Providing marketing training did not lead to additional adoption effects, although the study period may have been too short to measure these effects properly. This study is a first attempt to analyze how improved designs of agricultural extension can help to make smallholder farming more nutrition-sensitive. More research in this direction is needed.
Keywords: C93; O33; Q12; Q16; Q18; 330; agricultural extension; technology adoption; biofortification; nutrition-sensitive agriculture; Kenya